(untitled) - Schmidt, Arno (New York, 2003)
The Chef’s Book of Formulas, Yields, and Sizes is a powerful tool for controlling food costs in any foodservice operation. Now in an updated third edition, this encyclopedic reference is packed with helpful, practical information, including kitchen yields for more than 2,000 ingredients listed by food groups, sample purchase quantities, suggested serving sizes, tips and tricks for working with various ingredients, and other helpful tools for getting the most out of any size budget.
Keywords: Quantity cookery,Chất lượng nấu ăn